IMPLEMENTASI KEBIJAKAN PEMERINTAH TENTANG PENGALOKASIAN DANA PAJAK DARI PENERIMAAN PAJAK PENERANGAN JALAN TERHADAP PENYEDIAAN PENERANGAN JALAN UMUM DI KABUPATEN MINAHASA - Mangirang, Regina M.; Sondakh, Jullie J.; Lambey, Robert (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Earmarking Tax is the allocation of a certain amount of local revenue (especially tax) to fund public services in accordance with the type of tax levied. One type of tax from this policy is street lighting taxes whose funds are allocated for the provision of street lighting. Special street lighting tax no minimum amount should be allocated to ensure the availability of funds, then only adjust to the needs of the region. The purpose of this study is to analyze the implementation earmarking tax funds from street lighting tax revenue on the provision of street lighting in Minahasa District. The method used is qualitative descriptive method. From the research results can be seen that the policy of appropriation of tax funds has been applied in accordance with existing regulations in Minahasa regency as regulated in Minahasa District Regulation No. 1 of 2011 this is because more than a portion of funds from street lighting tax revenue has been allocated for the provision of lighting road that is equal to 57,55%. Earmarking tax in Minahasa District goes hand in hand with the APBD system, which is through the regional public treasury in terms of income and expenditure.Keywords: Earmarking Tax, street lighting tax.